(3QSGdI aj bdY GdBKGQs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3GdKhH jUjHI GdMHQ aYdi GdeGA hGdCTfGf LejYkG hjZeS GdKhH Lha GdCfGA GdPi jZdi ajgG GdeGA s
(3BNQgG (B:s
(3aEPG EHJd GdOe aCZSdg HUGHhf hEPG HGJ GdOe agj aCWd Ydjg OekG MGQkG hOYg SGYI Ke EZSdg HeGA MGQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs